Sorption Water By Modified Bentonite - Castrillo, Natalia Paola (2015)
In order to improve adsorptive properties and provide a viable alternative to humidity control techniques, the desiccants can be modified with chemical aggregates such as calcium chloride (CaCl2), the latter often used as dehydrating due to its hygroscopicity and low cost. Its use as a drying agent has disadvantages because of its particles form a liquid film. However, the CaCl2 may be mixed with other materials for preparing desiccant products. In this work we studied, at 298 K and different relative humidities (RH), the adsorption processes of desiccants mixtures composed of a bentonite clay Argentinian and CaCl2. The results showed a better performance of the desiccant mixture with respect to natural clay in the whole HR working range. It was also observed that addition of CaCl2 favors adsorptive properties with respect to a purification treatment.